Strategic Evaluation of Blood Donation Promotion Using the SWOT Analysis: A Systematic Model Transformation for Organizational Excellence - Waluyo Dwi Cahyono; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2026)
Maintaining a stable blood supply is a critical challenge for healthcare organizations in this dynamic era, necessitating a shift from routine operational management toward a more measured strategic management approach to achieve organizational excellence. This study aims to formulate a strategic model to increase blood donor participation using the SWOT (Strengths, Weaknesses, Opportunities, Threats) framework to map internal capacities and external opportunities in creating sustainable competitive advantage. Using a descriptive qualitative method through a systematic model, this study analyzes the SWOT Matrix to generate an integrative strategy between managerial efficiency and service innovation. The analysis results indicate that while the organization possesses strengths in its integrated donor database system, challenges such as medical hoaxes and limited marketing budgets remain the primary obstacles. Therefore, the recommended strategies include optimizing service digitization through mobile applications, strengthening corporate partnerships, and launching educational campaigns to counter negative stigma. In conclusion, the implementation of SWOT-based strategic management provides a clear direction for the organization in optimizing resources, which ultimately not only increases blood collection volumes but also drives the achievement of excellence standards in public health services